Residual flexural tensile strength of steel fibre reinforced concrete and steel fibre self-compacting concrete - Mohamed Syafiq Mohd. Shaharuddin, 1991-, author; Roslli Noor Mohamed, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2014